2013
DOI: 10.1136/bmjopen-2013-003341
|View full text |Cite
|
Sign up to set email alerts
|

The work of commissioning: a multisite case study of healthcare commissioning in England's NHS

Abstract: ObjectiveTo examine the work of commissioning care for people with long-term conditions and the factors inhibiting or facilitating commissioners making service change.DesignMultisite mixed methods case study research, combining qualitative analysis of interviews, documents and observation of meetings.ParticipantsPrimary care trust managers and clinicians, general practice-based commissioners, National Health Service trust and foundation trust senior managers and clinicians, voluntary sector and local governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…Guidance recommends using multiple sources of evidence to construct cases, including outcomes data to demonstrate potential cost savings, academic research and national guidelines. 53,66,88 Existing recommendations have also highlighted the importance of developing effective co-operation and communication between the stakeholders involved. Developing a multidisciplinary working group led by a clinical lead has been advocated as a means of achieving this.…”
mentioning
confidence: 99%
“…Guidance recommends using multiple sources of evidence to construct cases, including outcomes data to demonstrate potential cost savings, academic research and national guidelines. 53,66,88 Existing recommendations have also highlighted the importance of developing effective co-operation and communication between the stakeholders involved. Developing a multidisciplinary working group led by a clinical lead has been advocated as a means of achieving this.…”
mentioning
confidence: 99%
“…No studies of monitoring were identified. In relation to planning, there was a strong focus on the importance of comprehensive needs assessment for groups and populations Shaw et al 2013). Six studies addressed priority setting and rationing.…”
Section: Focus Of Studies On the Elements Of Commissioningmentioning
confidence: 99%
“…With respect to service use, Barnes et al (2013) found that in the context of inappropriate treatment of routine childhood (Baxter et al 2007; PCT case study); characteristics of commissioning managers (Checkland et al 2012; PCT); perceptions of value of priority-setting tools (decision support) for resource allocation (Marks et al 2011;PCTs); commissioning services for long-term conditions (Shaw et al 2013;PCTs); priority setting and rationing in PCTs (Robinson et al 2012; PCT case study); AFR framework to aid decision making (Bravo Vergel and Ferguson 2006;PCT); comparisons across commissioning models in Germany and UK (Sheaff et al 2013; PCT and other); views of CCG versus PCT commissioning (Turner et al 2013;PCT and CCG); are GPs best placed to deliver equity and excellence? Comparing GP commissioning with PCT (Gridley et al 2012; PCT and other); APMS contractual processes ; UK APMS); commissioning dental services through PDSS (Newton et al 2006; PDSS); barriers and enablers to commissioning ; PCT survey); engaging pharmacy in pharmaceutical needs assessment for commissioning pharmacy ; PCT) Quantitative: cluster RCT examining impact of commissioning on smoking cessation and entrance of new market players (McLeod et al 2015;PCTs); PBMA for purchasing (Wilson et al 2007; PCT) Mixed methods: redesigning children's services (Barnes et al 2013; PCT); use of external consultants by NHS commissioners (Naylor and Goodwin 2011; PCT interviews and survey); commissioners viewed HLP scheme as an effective model with which to deliver increased volume, quality and reliability of community health services (Kennington et al 2013; HLP) Fundholding practices (n = 1); PBC (n = 2); CCGs (n = 7) 1 quantitative; 9 qualitative 10 Quantitative: impact on cost containment and service use (Dusheiko et al 2006; fundholding) Qualitative: barriers to PBC (Checkland et al 2009; PBC); PBC as a service redesign tool (Slater and White 2007;PBC); investigating disinvestment practices (Rooshenas et al 2013;CCG); exploring development of CCG CCG); attitudes of GPs to commissioning including level of GP engagement with clinical commissioning and attitudes to incentives an...…”
Section: Evidence Of Impact Of Commissioningmentioning
confidence: 99%
See 2 more Smart Citations